Pola Sebaran Stunting di Kabupaten Jombang Tahun 2023 Menggunakan Analisis Geospasial - Dwi Regina Istiqlala; Mohamad Anis Fahmi (Ficco Scientific Corner, 2024)
Background: Stunting is a type of growth failure caused by inadequate nutrition, which lasts from pregnancy up to 24 months. This research aims to map the distribution of stunting prevalence in young children using the Geographic Information System (GIS). Methods: This study uses a descriptive cross-sectional type by collecting secondary data on stunting cases in young children obtained from the Jombang District Health Office in 2023. Results: Research using Moran's test shows that based on the results of autocorrelation data does not show the existence of significant local spatial autocorrelation at the level of stunting prevalence in Jombang Regency in the absence of statistical significance in the results of the LISA test, while the results of the distribution pattern of the Lisa cluster test are not significant, there is no strong evidence of the group areas that are close to the same and low stunting conditions in Kabuh and Megaluh districts. Conclusions: The prevalence of stunting in Jombang Regency in 2023 does not show a significant pattern of spatial autocorrelation based on the results of the LISA test. Suggestions: By using GIS technology, we can map the stunting areas and identify the most vulnerable community groups. This information will be very useful in designing a properly targeted intervention programme and improving the quality of life of the community.